PENGARUH CORPORATE GOVERNANCE TERHADAP EARNING MANAGEMENT DENGAN CAPITAL STRUCTURE SEBAGAI VARIABEL INTERVENING - Ricky Wijaya Shalim; Saarce Elsye Hatane (Business Accounting Review, 2017)
This research aimed to examine the affect of corporate governance to earning management with capital structure as an intervening variable. The sample used in this study comprised of corporations within trade and service sectors (whole-sale and retail sub-sectors) in Indonesia Stock Exchange (IDX) during 2010 to 2015. Data needed for this research is gathered from the 2010-2015 annual reports with a total of 115 observed reports. While the data analysis method used SPSS and WarpPLS software. The results showed that there was a significant negative correlation between the board meeting and board size which was an indicator of corporate governance towards earning management. The result of research also showed that board size had significant negative affect to capital structure, board meeting had significant positive affect to capital structure, and capital structure had significant negative affect on earning management.